PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM CENTERED LEARNING (PCL) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA DI KELAS VII SMP NEGERI 30 MAKASSAR - Alya Nabila; Pattaufi, Abdul Hakim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the effect of the implementation of the problem-centered learning (PCL) model on student learning outcomes in science subjects for grade VII students at SMP Negeri 30 Makassar. The fundamental problem of this study is that students feel bored during the learning process, are less active, and have difficulty understanding the material, which affects student learning outcomes. This study aims to: (1) determine the learning outcomes of grade VII students in science subjects before and after the implementation of the problem-centered learning (PCL) model, (2) determine the application of the problem-centered learning (PCL) model on student learning outcomes for grade VII students in science subjects at SMP Negeri 30 Makassar, (3) determine the effect of the application of the problem- centered learning (PCL) model on student learning outcomes for grade VII students in science subjects at SMP Negeri 30 Makassar. This study uses a quantitative approach with an experimental research type with a One Group Pre-test Post-test design using class VII.3 as the experimental class. The data collection process uses observation, tests (Pretest and Posttest), and documentation. The data analysis techniques used were descriptive statistical analysis and inferential analysis consisting of normality test, and hypothesis test using independent sample t-test. Student learning outcomes in the experimental class increased after being given treatment applying the problem centered learning (PCL) learning model. The results of this study indicate that the learning process by applying the problem centered learning (PCL) learning model was carried out well. There is a significant positive influence on the application of the problem centered learning (PCL) learning model on the learning outcomes of class VII students in science subjects at SMP Negeri 30 Makassar.